The Prognostic Impact of the Aryl Hydrocarbon Receptor (AhR) in Primary Breast Cancer Depends on the Lymph Node Status - Jeschke, Udo (Int J Mol Sci, 2019)
Increasing evidence implicates the aryl hydrocarbon receptor (AhR) as a possible regulator of mammary carcinogenesis. This study aims to clarify its prognostic impact in breast cancer (BC). Meta-analyses performed at the mRNA level demonstrated that the predictive value of AhR expression in BC depends on the lymph node (LN) status. AhR expression and sub-cellular location were then analyzed by immunohistochemistry in 302 primary BC samples. AhR was expressed in almost 90% of cases with a predominant nuclear location. Nuclear and cytoplasmic AhR levels were significantly correlated and associated with the expression of RIP140 (receptor-interacting protein of 140 kDa), an AhR transcriptional coregulator and target gene. Interestingly, total and nuclear AhR levels were only significantly correlated with short overall survival in node-negative patients. In this sub-group, total and nuclear AhR expression had an even stronger prognostic impact in patients with low RIP140-expressing tumors. Very interestingly, the total AhR prognostic value was also significant in luminal-like BCs and was an independent prognostic marker for LN-negative patients. Altogether, this study suggests that AhR is a marker of poor prognosis for patients with LN-negative luminal-like BCs, which warrants further evaluation.